Participatory Waste Management Governance in Small Island Tourism Destinations: A Case Study of Gili Trawangan - Rozikin, Mochammad; Prayana, Lalu Hendra; Tabali, Faisal Jamaludin (Journal of Governance and Social Policy, 2024)
This research investigates participatory governance in waste management within Gili Trawangan, a small island experiencing escalating waste generation due to tourism activities. A qualitative literature review reveals that resource limitations and inadequate environmental education hinder local community participation. Nevertheless, participatory approaches demonstrate significant potential in enhancing community awareness and capacity for sustainable practices. The findings underscore the importance of collaborative efforts, particularly engaging local businesses in the hospitality sector, to address the growing waste management demands. This study concludes that strengthening participatory governance through deeper engagement and adaptive policy interventions is crucial for optimizing waste management effectiveness in small island tourism contexts.